The Dip: The Extraordinary Benefits of knowing when to Quit (and When to Stick) - Seth Godin (Platkus, 2007)
Every new project (or career or relationship) starts out exciting and fun. Then it gets harder and less fun, until it hits a low point - really hard, really not fun. Winners quit fast, quit often and quit without guilt - until they commit to beating the right Dip for the right reasons. This book helps you do just that.